Improving the Operational Conditions of “ULUGNOR” Pump Station - Amrullo ugli, Mirzaev Mirzabek; Erkin ugli, Ergashev Xurshid (European Journal of Life Safety and Stability (2660-9630), 2021)
Today, the Republic of Uzbekistan is a leader in Central Asia in the use of pumping and power equipment for reclamation purposes at pumping stations. Therefore, ensuring the operation of pumping stations is a priority for the development of agriculture in our country. The location of agricultural lands in Uzbekistan in need of irrigation in arid zones (ie, low and unstable humidity) necessitates the use of regulated local flows for irrigation and so on. In modern conditions of use of reclamation systems it is necessary to take measures to prevent a decrease in the efficiency of irrigated agriculture.